2017
DOI: 10.1007/s11356-017-0206-9
|View full text |Cite
|
Sign up to set email alerts
|

Food safety aspects of primary environmental contaminants in the edible tissues of roe deer (Capreolus capreolus)

Abstract: The muscle, liver, kidney and fat samples of 20 roe deer of both sexes originating from a hunting area in central Hungary were investigated for the presence of heavy metals such as As, Cd, Hg and Pb, and their contents were evaluated for possible health risk to consumers. Both As and Hg were found at a level below the limit of detection (< 0.5 mg/kg wet weight) in all samples. The median of the measured Cd concentrations was significantly higher in both the kidney and the liver (p = 0.0011) of bucks than of do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…However, the differences in the cited study were insignificant, and sex could not be regarded as a variable determining the concentration of elements. On the other hand, Lehel et al ( 2017 ) confirmed the effect of sex on the levels of Cd and Pb in the liver, muscle and kidneys of roe deer and found that Cd concentrations were higher in all organs and muscle of male animals, while Pb concentrations were higher in the liver and kidneys of female animals. No significant sex-related differences in the levels of Pb in meat were reported by Lehel et al ( 2017 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the differences in the cited study were insignificant, and sex could not be regarded as a variable determining the concentration of elements. On the other hand, Lehel et al ( 2017 ) confirmed the effect of sex on the levels of Cd and Pb in the liver, muscle and kidneys of roe deer and found that Cd concentrations were higher in all organs and muscle of male animals, while Pb concentrations were higher in the liver and kidneys of female animals. No significant sex-related differences in the levels of Pb in meat were reported by Lehel et al ( 2017 ).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, Lehel et al ( 2017 ) confirmed the effect of sex on the levels of Cd and Pb in the liver, muscle and kidneys of roe deer and found that Cd concentrations were higher in all organs and muscle of male animals, while Pb concentrations were higher in the liver and kidneys of female animals. No significant sex-related differences in the levels of Pb in meat were reported by Lehel et al ( 2017 ). The specific effect of sex on the absorption and metabolism of pollutants in the body may result from the differences between females and males at almost all levels, including gene expression and biochemistry, physiology, morphology and ontogeny (Burger 2007 ; Legras et al 2000 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In another study, an average of 0.0078 mg/kg of cadmium was obtained in wild boar muscle, which may be like ours at a lower detection limit (Danieli et al 2012 ). Values below the LOD findings were noted in the muscle samples of roe deer ( Capreolus capreolus ) (Lehel et al 2016a , b ), not much differently in the muscle of roe bucks 0.04 ± 0.02 mg/kg (Lehel et al 2017 ). However, higher residue was detected in liver and kidney in both bucks (0.13 ± 0.04 mg/kg; 1.03 ± 0.52 mg/kg) and does (0.03 ± 0.02 mg/kg; 0.21 ± 0.20 mg/kg) (Lehel et al 2017 ).…”
Section: Resultsmentioning
confidence: 96%
“…Due to its redox activity, it has a detrimental effect on the antioxidant system, causes oxidative stress, increases lipid peroxidation, and changes the lipid composition of the membrane (Xu et al 2003 ; Nair et al 2013 ; Lehel et al 2016a , b ). The highest amounts of Cd can be measured in the kidneys and liver of food-producing animals (Laczay 2015 ; Lehel et al 2017 ).…”
Section: Cadmium (Cd)mentioning
confidence: 99%